IMPLEMENTATION OF GUIDANCE AND COUNSELING IN CREATING A PANCASILA STUDENT PROFILE AT SDN 13 PARIT PUTUS, AMPEK ANGKEK DISTRICT - Eni Oktavia; Ulil Azmi; Destria Sudirman (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The Merdeka Curriculum is a curriculum that contains the Pancasila student profile. The main characteristics of Pancasila students include faith, devotion to God Almighty, noble morals, global diversity, mutual cooperation, independence, critical thinking and creativity. These six profiles are formed through teaching and advice in elementary school classes. The aim of orientation and teaching activities is to develop students' personalities in accordance with the unique curriculum requirements implemented at school. This article describes the implementation of orientation and counseling activities carried out at SDN 13 Parit Putus with the aim of realizing the profile of Pancasila students in elementary schools. The results of the research show that SDN 13 Parit Putus does not yet have experts in the field of guidance and advice, but the implementation of guidance and advice has been well integrated in all activities that take place in learning and at school, especially in daily habituation activities. This shows that students who become Pancasila students are able to apply Pancasila values in everyday life.